Giant ventral hernia immediately after vaginal twin delivery - B. Kim; S.H. Hong; J.H. Kim; M.Y. Kang; M.R. Rhee; J. Kim; K.J. Kim; H.A. Lee (IMR Press, 2020)
Introduction: Giant ventral hernia immediately after vaginal twin delivery is a rare event and the management is unclear. Case presentation: A 28-year-old primiparous woman had a spontaneous vaginal preterm twin delivery at gestational age 36 weeks and 5 days, followed by a giant ventral hernia with severe pain. She had a single-incision laparoscopic cholecystectomy two years earlier. She was closely monitored with transfusion and pain control, and improved spontaneously without emergency surgery. Conclusion: Immediately after vaginal twin delivery, a giant ventral hernia was detected in a 28-year-old primiparous woman who had a history of single-incision laparoscopic cholecystectomy. Fortunately, the hernia resolved spontaneously without the need for emergency surgery.